Factors that Influence Freedom of Speech and Self-censorship in Mass Media in Contemporary Russia - Olshevskaya, Oksana (Žurnalistikos tyrimai, 2015)
An attempt to define the degree of media freedom in contemporary Russia leads to contradiction between the declaration of the mass media freedom provided by the Constitution of the Russian Federation and the Soviet Union heritage of unequivocal control of the press by the government, described by Siebert et al. (1984) as the Soviet-Communist Press Theory. The reason for this ambiguity could be explained by the great deal of different factors that exert an influence on the journalism, such as features of mass media legislation, governmental control of the media, the diversity of media ownership, sources of media incomes, and traditions of censorship in Russia. The current development of the media legislation in Russia shows no improvement regarding the freedom of speech. In the beginning of the third presidential term in 2012, Vladimir Putin has signed several laws that reduced the freedom of speech through the limitation of public assembly, criminalization of defamation in the mass media, and intensification of governmental censorship on the internet. On the other hand, the contemporary press freedom that appeared in conditions of the new market economy in the beginning of the 1990s has brought discredit as to the conception of an exclusively positive impact of unconditional freedom on the mass media since the newspapers, television and radio channels were controlled by several powerful oligarchs who used the owned mass media to spread and support their political influence. However, after the authorities’ reference in the 2000s the balance was not regained. As a result, the majority of the media outlets in Russia became co-owned or fully controlled by the government. Another crucial aspect of the mass media freedom as the cultural phenomenon should be kept in mind: seven decades of severe censorship could not be erased from the journalism professional community’s memory in several years. The negative experience of predecessors transforms censorship into self-censorship in modern Russia.